ENGLISH TRAINING PROGRAM THROUGH DEBATE METHOD FOR TEACHERS OF SMKN 1 SINGOSARI MALANG - Wibowo, Arining (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
The aim of this training is to teach English language teachers of Vocational High School/SMKN 1 Singosari Malang. The absolute role of English as a medium of communication and learning for vocational students is undeniable. Vocational High School is dedicated to produce technical worker which they are prepared to be readily working after graduated without continuing to study on college degree. By having English language as their fluent second language, alumnus will have big weapon to compete in the current bothersome job demand. Problem of teaching-learning English is the one background of this training. English Debate method is a new method in SMKN 1 which they are introduced various techniques to learn English. By this method, teachers will be talented to teach English to students actively and innovatively. The result of this training told us that English Debate is effective method to be applied on teaching-learning English especially on speaking.